Systematic review with meta‐analysis: the adverse effects of tobacco smoking on the natural history of Crohn's disease. Issue 5 (7th January 2016) - To, N.; Gracie, D. J.; Ford, A. C.
Summary: Background: Tobacco smoking is a well‐established risk factor for the development of Crohn's disease, and this may lead to a more complicated disease course. However, recent evidence suggests that many patients with Crohn's disease are unaware of this fact. Aim: To perform a systematic review and meta‐analysis of the effects of smoking on disease course in Crohn's disease. Methods: A search of MEDLINE, EMBASE and EMBASE classic was carried out (up to July 2015) to identify observational studies reporting data on smoking and rates of surgery or flares of disease activity in patients with Crohn's disease. Dichotomous data were pooled to obtain odds ratios (ORs) for flares of disease activity or need for surgery, with 95% confidence intervals (CIs). Results: The search identified 33 eligible studies. Compared with nonsmokers, smokers had increased odds of flare of disease activity (OR, 1.56; 95% CI, 1.21–2.01), flare after surgery (OR, 1.97; 95% CI, 1.36–2.85), need for first surgery (OR, 1.68; 95% CI, 1.33–2.12) and need for second surgery (OR, 2.17; 95% CI, 1.63–2.89). The odds of these outcomes among ex‐smokers diminished upon smoking cessation, with ORs comparable to those among nonsmokers and, in the case of flare or second surgery, significantly lower than smokers. Conclusions: Smokers with Crohn's disease have a more complicated disease course than nonsmokers, and quitting smoking may ameliorate this. Patients should be reminded of the detrimental effects of smoking on the course of their disease, and smoking cessation advice should be provided to reduce disease burden and costs in these patients.